Impacts of La Niña on Sea Surface Temperature, Chlorophyll-a, and Fishery Productivity in Northern East Java Ocean - Bahtiar, Ahmad; Yulfiah, Yulfiah (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
The La Nina phenomenon occurs when the sea surface temperature in the Northeast Pacific Ocean becomes colder. Meanwhile, temperatures in the Western Pacific Ocean are warmer than usual. Such conditions affect the oceanographic conditions of Indonesia's waters, including the Northern Waters of East Java. Therefore, it is necessary to conduct research aimed at analyzing the impact of the La Nina phenomenon on the fertility of the Northern Waters of East Java, through observations of sea surface temperature (SST) distribution, chlorophyll-a concentration, and fish catch data. SST data and chlorophyll-a concentration were obtained from Aqua-MODIS satellite images and analyzed using quantitative methods. Meanwhile, fish catch data were obtained from seven fishing ports on the North Coast of East Java. The results showed that the SST cycle in East Munson was not affected by the La Nina phenomenon. However, La Nina affects the ever-increasing SST anomaly value. The SST cycle in West Munson decreased in the La Niña period. Chlorophyll-a anomaly values also decreased during the La Nina period, especially from October 2017 to April 2018. Chlorophyll-a anomaly values tend to increase in the La Nina period from August 2020 to December 2022. This is influenced by the IOD (-) period. There was a time lag in the effect of SST and chlorophyll-a on fish catches. During La Nina, fertility rates in the Northern Waters of East Java tend to be low, marked by warming sea surface temperatures, uneven distribution of chlorophyll-a, and reduced fish catches. Such conditions can be taken into consideration in the planning of mitigation measures for the impacts of La Niña in the maritime and fisheries sectors in the upcoming period.